2004
DOI: 10.1093/ajcn/80.6.1508
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant vitamins and coronary heart disease risk: a pooled analysis of 9 cohorts

Abstract: The results suggest a reduced incidence of major CHD events at high supplemental vitamin C intakes. The risk reductions at high vitamin E or carotenoid intakes appear small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
143
2
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 257 publications
(160 citation statements)
references
References 59 publications
5
143
2
10
Order By: Relevance
“…58 However, in this pooled analysis, supplemental vitamin C (400 mg/d) was associated with a 25% reduction in incident coronary heart disease in comparison with that noted for nonusers of vitamin C supplements (P < .001). Adjustments for ''healthy'' lifestyle and potential dietary confounders did not weaken this association.…”
Section: Cardiovascular Diseasementioning
confidence: 59%
“…58 However, in this pooled analysis, supplemental vitamin C (400 mg/d) was associated with a 25% reduction in incident coronary heart disease in comparison with that noted for nonusers of vitamin C supplements (P < .001). Adjustments for ''healthy'' lifestyle and potential dietary confounders did not weaken this association.…”
Section: Cardiovascular Diseasementioning
confidence: 59%
“…This mechanism explains to some extent why HDL-C is an independent risk factor to LDL-C for CVD Stampfer et al 1996;Chapman et al 2011;Miller et al 2011). Antioxidants such as Vitamins E and C can slow the damage, but they only delay the peroxidation on the scale of minutes not hours (Esterbauer et al 1992), consistent with the demonstrated weak effect of antioxidant use in cohort trials and the failure of antioxidant therapy to control atherosclerosis in random control trials (Jha et al 1995;Knekt et al 2004). Once the plaque forms, inflammatory immunological processes are engaged (Stocker and Keaney 2004), and anti-inflammatory and anti-platelet treatment can reduce the risk of vascular death (Bousser et al 2011).…”
Section: The Development Of Cardiovascular Diseasementioning
confidence: 83%
“…Indeed, Knekt et al [104] found vitamin E and carotenoids lacked efficacy in the prevention of cardiovascular diseases, but they noted a significant decrease in frequency of coronary artery disease and other serious cardiac events in sick persons supplemented with large doses of vitamin C (> 700 mg/d). A meta-analysis by Wright et al [105] showed, however, that a long-term intake rich in dietary and/or supplemental vitamin E significantly reduces mortality from coronary artery disease and from ischemic stroke, as well as all-cause mortality.…”
Section: Meta-analysis Of Results Of Studies On the Effectiveness Of mentioning
confidence: 99%